Family disputes in administration of estates: analysis on mediation as effective dispute resolution mechanism in Malaysia - Nasrul, Muhammad Amrullah; Md Said, Muhamad Helmi; Abdul Hak, Nora; Mohd Salim, Wan Noraini (Malaysian Journal of consumer and Family Economics Association, Universiti Teknologi Mara, 2019)
A family dispute is one of the issues that occur in the administration of the deceased’s estate. Such dispute may happen at any stage in estate administration, ranging from the application of letters of representation until the distribution of the deceased’s asset. The occurrence of family dispute tends to affect the administration adversely and may lead to delay in the distribution which at the same time rendered the process incomplete. However, despite the seriousness of family dispute in estate administration, there is no specific method in resolving the problem apart from the litigation process. Litigation is less preferred in this case due to its inability to address the emotional grief suffered by the parties. Plus, it is time consuming and has a relatively expensive cost. Mediation, on the other hand, is seen as a potential dispute resolution mechanism thanks to its effective method in addressing the core issues in a family dispute. This paper addresses the overview of a family dispute as well as analyses mediation in addressing and resolving the issue in the administration of a family estate. The study undertakes a library-based study as a selected research method through the analysis of selected materials including journal articles, textbooks, statutes as well as interview method. Findings from this paper indicate that mediation excels in resolving family disputes due to its ability to relieve the emotional distress suffered mainly by the beneficiaries. It is suggested that the administrative bodies primarily, should start to take the initiative in introducing mediation as an effort to improve the process of estate administration in Malaysia.